Rancang Bangun Aplikasi Evaluasi Beban Kerja Tenaga Kesehatan Berdasarkan Metode Workload Indicator Staffing Need - Andreas Catur Pamungkas; Haryanto Tanuwijaya; Yoppy Mirza Maulana (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Public health center of Jagir Surabaya is a functional health organization under working units of Surabaya City Health Department. Public health center of Jagir Surabaya also a center for the development of public health services in charge of organizing health development in the District Jagir. During the calculation of the workload carried is based solely on the amount of volume on description of duties and responsibilities carried out at one of the health workers. Whereas in fact, the calculation of the workload of health workers who do need to refer to the Guidelines for Preparation of HR planning by using WISN (Work Load Indicator Staffing Need) as determined by the Minister of Health to serve as guidelines and are implemented by all Unit Health Services (including hospitals).Therefore, these problems need to be created a system that can help the public health center of Jagir in conducting the process of calculating the workload of health workers based on the method WISN.Based on the results of testing and evaluation, it is known that the application evaluation of health workers workload with methods WISN can help the public health center of Jagir to perform the calculation and reporting of the amount of labor requirements of health and be able to support later in the planning process of health personnel so as to improve the quality and the health service public health center of Jagir Surabaya